ANALISIS PERILAKU ANGIN DI LAPISAN 850 hPa HASIL OBSERVASI DATA WPR DIKAITKAN DENGAN PERILAKU DATA INDEKS MONSUN GLOBAL DI INDONESIA - Noviyanti Erfien Kaparang; Eddy Hermawan (Jurnal Sains Dirgantara, 2010)
This study analyzed the behavior of winds in the lower layers of the troposphere, or rather at "approximately" 850 hPa layer, which is equivalent to an altitude of "about" 1.5 km above the sea level (asl) and observed the data at Wind Profiling Radar (WPR) in Pontianak, Biak, Manado, Serpong and Kototabang, particularly in the wet months (BB) and dry months (BK) for a few months. The results show that the WPR data used to identify the Monsoon on the Indonesian Maritime Continent region (BMI) is quite refresentative. The results further show that the cities which are located relatively close to the equatorial line, such as Pontianak and Biak are relatively strongly influenced by wind zonal (East-West). While the city which is relatively far from the equatorial line (like Manado), is relatively strongly affected by the meridional wind (North-South). There is further analysis of why this is happening. However, this is allegedly due to the influence of Coriolis force (Coriolis Force), particularly at the lower layers of the troposphere in the region that is located relatively far from the equatorial than in the precise area at the equatorial considering that the Coriolis force itself is close to zero (very small) for the equatorial region. Another interesting point is that the zonal winds are stronger influence on the data AUSMI (Australian Monsoon Index), while the meridional winds are the stronger influence on the data WNPMI (Western North Pacific Monsoon Index) with correlation values respectively around 0.76 and 0.45. Keywords: Monsoon Signal, WPR, and Global Monsoon Index